CCR5‐Δ32 polymorphism—a possible protective factor from gait impairment amongst post‐stroke patients. (3rd December 2022) - Molad, Jeremy; Hallevi, Hen; Seyman, Estelle; Rotschild, Ofer; Bornstein, Natan M.; Tene, Oren; Giladi, Nir; Hausdorff, Jeffrey M.; Mirelman, Anat; Ben Assayag, Einor
Abstract: Background and purpose: Stroke and small vessel disease cause gait disturbances and falls. The naturally occurring loss‐of‐function mutation in the C‐C chemokine receptor 5 gene ( CCR5 ‐Δ32) has recently been reported as a protective factor in post‐stroke motor and cognitive recovery. We sought to examine whether it also influences gait and balance measures up to 2 years after stroke. Method: Participants were 575 survivors of first‐ever, mild–moderate ischaemic stroke or transient ischaemic attack from the TABASCO prospective study, who underwent a 3 T magnetic resonance imaging at baseline and were examined by a multi‐professional team 6, 12 and 24 months after the event, using neurological, neuropsychological and mobility examinations. Gait rhythm and the timing of the gait cycle were measured by force‐sensitive insoles. CCR5 ‐Δ32 status and gait measures were available for 335 patients. Results: CCR5 ‐Δ32 carriers (16.4%) had higher gait speed and decreased (better) stride and swing time variability 6 and 12 months after the index event compared to non‐carriers ( p < 0.01 for all). The association remained significant after adjustment for age, gender, education, ethnicity and stroke severity. Conclusions: Significant associations were found between gait measurements and CCR5 ‐Δ32 loss‐of‐function mutation amongst stroke survivors. This is the first study showing that genetic predisposition may predict long‐term gait function after ischaemic stroke.